User perception on electronic customer relationship management (E-CRM) features in online hotel reservation / Hasliza Azizan - Azizan, Hasliza (Faculty of Computer and Mathematical Sciences, 2007)
In the hotel industry, the internet plays to grow an important role as a core distribution channel in management sector. From a global perspective hotels are at varying stages of managing their direct and indirect channels to markets and are adopting different strategies to reach customer satisfaction, sales, profit and their loyalty. Some hotels have yet to develop all available distribution channels while others are encouraging customers to book through the most effective channel by booking via online. Due to these phenomena, this research was conducted to identify the customers' perception towards the electronic customer relationship management (E-CRM) features of hotel online service quality. Through all the E-CRM features application, the services can be enhanced, instead of offering customers convenience, personalization in information, customization site and other accommodation information is integrated. Thus are presented from the customer experience and their interaction with a website. Responding to the phenomena, this research also wants to gain deeper understanding regarding the services by using 42 features of E-CRM application. The research also comprised the influences of ECRM features and their relationship between the 9 dimensions in the E-CRM.